Development of Katar-Bio: Smart Card-Based Interactive Media to Improve of Second-Grade XI Students' Understanding and Motivation in Respiratory System Topics - Fitriya Handayani; Rohani Rohani (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: The issue of low conceptual understanding and learning motivation among students in the respiratory system topic highlights the need for more interactive and engaging learning media innovations. This study aims to develop an interactive learning medium based on biology smart cards (Katar-Bio) to enhance Grade XI students' conceptual understanding and learning motivation. Methodology: The study employs the 4-D development model (Define, Design, Develop, and Disseminate), involving 30 students from class XI MIA1 at SMA Swasta Budi Agung Marelan. The research instruments include expert validation sheets, student and teacher response questionnaires, a learning motivation scale, as well as pretest and posttest items. Findings: The development stages consist of needs analysis, media design, expert validation, practicality testing, and effectiveness evaluation. Expert validation results yielded feasibility scores of 95% for media and 79% for content. The practicality level was categorized as very high, with student responses at 92% and teacher responses at 96%. The effectiveness of the media was measured using the N-Gain formula, resulting in a score of 0.80 (high category), indicating a significant improvement in conceptual understanding. Additionally, there was a 31.45% increase in students' learning motivation after using the media. These findings demonstrate that Katar-Bio media positively contributes to the learning process, both academically and motivationally. The media is also equipped with QR codes linked to instructional videos and online quizzes to enhance interactivity. Contribution: The academic implications of this study suggest that Katar-Bio can be widely implemented and adapted for other biology topics. Scientifically, this medium integrates digital technology through QR codes into smart cards, making it an innovative learning approach that has not been widely applied in teaching the respiratory system topic